Seismic study of 1/4 scale Unreinforced adobe masonry models Retrofitted with pp-band meshes - Sathiparan, N.; Mayorca, P.; Meguro, K. (My University, 2010)
This paper introduces a technically feasible and economically affordable PP-band (polypropylene band) retrofitting for low earthquake resistant masonry structures in developing countries. Results of the shaking table tests on building models show that the PP-band retrofitting technique can enhance safety of both existing and new masonry buildings even in worst case scenario of earthquake ground motion like JMA7 seismic intensity. Therefore proposed method can be one of the optimum solutions for promoting safer building construction in developing countries and contribute earthquake disaster mitigation in future.
Keywords: adobe masonry; polypropylene band